JUMLAH KUNJUNGAN ANTI NATAL CARE MENENTUKAN TEMPAT PERSALINAN - Puspitasari, Dian (Universitas Jenderal Achmad Yani Yogyakarta, 2014)
Background: âDesa Siagaâ is one of the programs of the community empowerment in order to increase the coverage of delivery by health provider in health facilities especially in sub-district of Kaliangkrik district Magelang. This was due to the under utilization of health facilities by community. This study aimed to analyze the number of ANC visits in delivery site selection. Methods: This research was a cross sectional analytic approach with 130 respondents. Data were collected using validated and realible questionnaire conducted from November to December 2012. Data were analyzed using univariate and bivariate with Chi-Square. Result: The results showed 70 respondents who chosed home birth (82.4%) and number of ANC visits (p<0.001), Number of ANC visits showed the strongest influence on the delivery site selection. This study concluded that there is relationship between number of ANC visits with delivery site selection in âDesa Siagaâ at sub-district of Kaliangkrik district Magelang. Conclusion: The community health center is expected to encourage the number of ANC visit to increase the coverage of health delivery in village health facility. Keywords: âDesa Siagaâ, delivery site selection, number of ANC visits